SLAUGHTER HOUSE SOLID WASTE MANAGEMENT IN INDONESIA - Rhenny Ratnawati; Yulinah Trihadiningrum (The East Java Biological Society, 2014)
he solid slaughter house waste (SSW) in Indonesia is generally disposed of into open dumped landfill. This type of solid waste can cause odor and atmospheric pollution if discharged directly into the environment. Additionally, it may spread disease due to the nesting vectors, and the resulting leachate can lead to groundwater contamination. This paper reviews the characterization of slaughter house (SH) types and SSW generation potential and to review the development of treatment technology of SSW and its application. The SH in Indonesia is divided into 3 classes, namely: 1) SH for large and small ruminants; 2) SH for poultry; 3) SH for pigs. Application technologies in Indonesia include compost and biogas technologies, and the use of rumen content for animal feed. Problem in biogas technology is generally caused by the high nitrogen content in the SSW. The most suitable raw material for biogas production is herbivore waste. The main advantages of using SSW for compost production are: the appropriate characteristics for composting process, free of hazardous contaminant, and appropriate composting technologies are available to reduce environmental problems caused by SSW. In addition, rumen content is considered to be a potential alternative for animal feed because have high content of amino acids (approximately 73.4% of the total protein) and rich in vitamin B complex. Among the disadvantages, the composting process of SSW requires long time period and generate air pollutants, such as ammonia and hydrogen sulphide.